Fat source effects on finishing steer digestion and metabolism - B.J. Bock; D.L. Harmon; Robert T. Brandt Jr.; J.E. Schneider (Kansas Agricultural Experiment Station Research Reports, 1990)
A replicated 3 x 3 Latin square design was used to explore the effects of fat source (none vs 3.5% soybean oil soapstock or animal tallow) when fed with high (1.0%) calcium on digestion and metabolism of a finishing diet by steers. Adding fat did not affect site or extent of starch or dry matter digestion. A net synthesis of long chain fatty acids occurred in the rumen. Feeding fat tended (P=.ll) to depress bacterial N flowing at the duodenum but did not affect nonbacterial N or total N.
Keywords: Cattlemen' s Day; 1990; Kansas Agricultural Experiment Station contribution; no. 90-361-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 592; Beef; Digestibility; Fat; Calcium; Finishing